2011
DOI: 10.1523/jneurosci.3335-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory Retrieval, Parietal Cortex, and the Default Mode Network: Functional and Topographic Analyses

Abstract: The default mode network (DMN) is often considered a functionally homogeneous system that is broadly associated with internally directed cognition (e.g. episodic memory, theory of mind, self-evaluation). However, few studies have examined how this network interacts with other networks during putative “default” processes such as episodic memory retrieval. Using fMRI, we investigated the topography and response profile of human parietal regions inside and outside the DMN, independently defined using task-evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
327
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(390 citation statements)
references
References 63 publications
51
327
3
5
Order By: Relevance
“…network, and fMRI studies of episodic memory retrieval have reported robust functional dissociation within the default mode network: Posterior regions (angular gyrus, posterior cingulate/precuneus) were active during memory retrieval, whereas anterior regions (prefrontal cortex) were inactive (Sestieri et al, 2011). Additional fMRI studies provided further evidence in support of these findings regarding the default mode network (Damoiseaux et al, 2008;Lei et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 73%
“…network, and fMRI studies of episodic memory retrieval have reported robust functional dissociation within the default mode network: Posterior regions (angular gyrus, posterior cingulate/precuneus) were active during memory retrieval, whereas anterior regions (prefrontal cortex) were inactive (Sestieri et al, 2011). Additional fMRI studies provided further evidence in support of these findings regarding the default mode network (Damoiseaux et al, 2008;Lei et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 73%
“…The angular gyrus is an important hub of the posterior part of the DMN which has been shown to be active during memory-based decision making (Sestieri et al 2011) and semantic processing (Seghier et al 2010). In a lexical decision task (discriminating words from nonwords) including the instruction to refocus on breathing after each decision, Zen meditators showed a shortened post-stimulus tail and decreased post-stimulus left angular gyrus BOLD activity compared to controls (Pagnoni et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The attentional account of PPC retrieval effects, while conceptually attractive at a number of levels, has been challenged by recent meta-analytic (Hutchinson et al 2009) and withinstudy (Sestieri et al 2010(Sestieri et al , 2011 evidence that suggests that the PPC subregions associated with top-down and bottom-up attention are anatomically separable from those associated with episodic retrieval (see also Shannon and Buckner (2004) for evidence of further visuospatial attention/retrieval dissociations). For example, drawing on the published attention and memory literatures, Hutchinson et al (2009) systematically assessed the overlap in PPC between effects of top-down and bottom-up attention and those of item memory strength and recollection.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of PPC functional specialization during episodic retrieval also requires consideration of the growing literature demonstrating that PPC contains a mosaic of subregions, each with unique connectivity, functional properties, and receptor composition (Zilles and Palomero-Gallagher 2001;Grefkes and Fink 2005;Silver and Kastner 2009;Uddin et al 2010;Uncapher et al 2010;Nelson et al 2010;Mars et al 2011;Sestieri et al 2011;Yeo et al 2011;Caspers et al 2012). In light of the debate regarding PPC contributions to attention and memory, a particularly relevant aspect of this recent research has been the discovery and characterization of topographically organized maps of attended visual space in IPS and SPL (for review, see Silver and Kastner 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation